Fibre bridging: Continuum modelling of extrinsic toughening in double cantilever beam tests. (September 2022) - Huxford, Bobby; Ronan, William; Russell, Benjamin P
Extrinsic toughening, such as fibre bridging, acts behind the crack tip to increase toughness in composite laminates. Computational studies have captured this phenomenon; however, the uniqueness of fit between computational results (which vary based on the interface traction-separation relationship) and experimental results has not been explored in detail. Here, detailed exploration of the parameter space for various traction-separation laws (TSL) using finite elements is presented to investigate the role of fibre bridging. In the absence of extrinsic toughening, a linear softening TSL is sufficient to capture the key R-curve features, the total input fracture energy is of primary importance. Where extrinsic toughening is present, the ratio between intrinsic and extrinsic energy dictates the shape of the crack growth resistance curve (where fracture toughness (energy) increases with increasing crack growth). The influence of fibre bridging length on the crack growth required to reach a plateau in toughness is examined. A strategy for determining key cohesive properties from a double cantilever beam test is presented and applied to experimental results.